A Schistosoma japonicum MicroRNA Exerts Antitumor Effects Through Inhibition of Both Cell Migration and Angiogenesis by Targeting PGAM1 - Hu, Chao; Li, Yuzhen; Pan, Danting; Wang, Jing; Zhu, Liufang; Lin, Yu; Zhu, Shanli; Pan, Weiqing (Frontiers in Oncology, 2021)
MicroRNA (miRNA) is an important regulator for gene expression. Recent studies showed that some heterogenous miRNAs derived from both parasite and plant can regulate expression of mammalian gene in a cross-species or even a cross-kingdom manner. Here, we identified a Schistosoma japonicum miRNA (designated as sja-miR-61) that is present in the hepatocyte of mice infected with the parasite. The sja-miR-61 mimics significantly inhibited the migration of both mouse and human hepatoma cells in vitro. In a xenograft animal model, significant reductions of the tumor volume and weight was observed in mice inoculated with hepatoma cells transfected with sja-miR-61 mimics compared to the controls. We found that the in vivo inhibition of tumor growth was through its anti-angiogenesis activity. Mechanically, we identified the phosphoglycerate mutase 1 (PGAM1) gene as a target of sja-miR-61 and found that the sja-miR-61-mediated suppression of cell migration and anti-angiogenesis by cross-species down-regulation of PGAM1 expression. These data indicated that sja-miR-61 is a tumor suppressor miRNA that may have therapeutic potential for human cancers.